ANALISIS PROSES PEMECAHAN MASALAH MATEMATIS SISWA SMP MELALUI PROJECT BASED LEARNING BERDASARKAN ADVERSITY QUOTIENT - Asmana, Arezqi Tunggal; Nugroho, Ariq Naufal (WAHANA PEDAGOGIKA: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
The purpose of this study was to determine the process of solving mathematical problems based on students' Adversity Quotient. This research was conducted in class VIII B of MTs Tanwirul Qulub for the 2021/2022 Academic Year. The subjects consisted of 6 people, namely 2 students in the climber category, 2 students in the camper category, and 2 students in the quitter category. Data collection techniques used were pre-test, post-test, questionnaires and interviews. The questionnaire was used to find out the Adversity Quotient of students based on the 3 categories as a whole. Based on the results of the research, it can be seen that the process of solving students' mathematical problems based on the Adversity Quotient for the climber, camper, and quitter categories has different processes. Students based on the Adversity Quotient in the climber category are able to carry out the process of solving mathematical problems well on 4 problem solving indicators with the maximum which results in success in solving the problems they face. Students based on the Adversity Quotient in the camper category are able to understand the problem well, plan the correct solution to the problem, carry out the settlement plan well, but are not optimal in checking again. Students based on the Adversity Quotient quitter category have not fulfilled the four indicators of mathematical problem solving.